Disruption of Telomere Integrity and DNA Repair Machineries by KML001 Induces T Cell Senescence, Apoptosis, and Cellular Dysfunctions - Cao, Dechao; Zhao, Juan; Nguyan, Lam N.; Nguyen, Lam N. T.; Khanal, Sushant; Dang, Xindi; Schank, Madison; Chand Thakuri, Bal K.; Wu, Xiao Y.; Morrison, Zheng D.; El Gazzar, Mohamed; Zou, Yue; et al. (Frontiers in Immunology, 2019)
T cells in chronic viral infections are featured by premature aging with accelerated telomere erosion, but the mechanisms underlying telomere attrition remain unclear. Here, we employed human CD4 T cells treated with KML001 (a telomere-targeting drug) as a model to investigate the role of telomere integrity in remodeling T cell senescence. We demonstrated that KML001 could inhibit cell proliferation, cytokine production, and promote apoptosis via disrupting telomere integrity and DNA repair machineries. Specifically, KML001-treated T cells increased dysfunctional telomere-induced foci (TIF), DNA damage marker γH2AX, and topoisomerase cleavage complex (TOPcc) accumulation, leading to telomere attrition. Mechanistically, KML001 compromised telomere integrity by inhibiting telomeric repeat binding factor 2 (TRF2), telomerase, topoisomerase I and II alpha (Top1/2a), and ataxia telangiectasia mutated (ATM) kinase activities. Importantly, these KML001-induced telomeric DNA damage and T cell senescent phenotype and machineries recapitulated our findings in patients with clinical HCV or HIV infection in that their T cells were also senescent with short telomeres and thus more vulnerable to KML001-induced apoptosis. These results shed new insights on the T cell aging network that is critical and essential in protecting chromosomal telomeres from unwanted DNA damage and securing T cell survival during cell crisis upon genomic insult.